Diagnostic Accuracy of Ultrasound Elastography in Meniscus Assessment: A Comparative Analysis with Magnetic Resonance Imaging - Karadayı Büyüközsoy, Ayşegül; Voyvoda, Nuray; Fariz, Burak; Özer, Tülay (Cerrahpaşa Medical Journal, 2024)
Objective: Ultrasonography (US) is a non-invasive, non-ionizing radiation modality which is highly successful at diagnosing meniscal pathologies. The aim of this study is to demonstrate the contribution of strain elastography (SE) to diagnosis by comparing SE and B-mode US findings of the meniscus with magnetic resonance imaging (MRI). Methods: A total of 22 patients (a total of 30 knees) who presented to the department of sports medicine with knee pain were included the study. All menisci of the 33 knees were evaluated by B-Mode US, SE, and MRI. The result of US, SE and MRI were compared each other. Pearson and Spearman correlation tests were used to evaluate the inter-technique correlation. Results: The US and MRI findings of medial meniscus anterior horn (MMAH), medial meniscus posterior horn (MMPH), lateral meniscus anterior horn(LMAH), lateral meniscus posterior horn(LMPH) were correlated (P < .001, P < .001, P = .002, P = .006). For the evaluation of MMAH and LMPH, the sensitivity of US was 100%, and the specificity was 87% and 80%, respectively. There was a negative correlation between strain ratio (SR) and both of US and MRI injury grades for MMAH, MMPH, and LMPH (r = −0.389 and r = −0.499 for MMAH; r = −0.045 and r = −0.441 for MMPH; r = −0.307 and r = −0.691 for LMPH, respectively). There was a negative correlation between SR and US injury grade for LMAH (r = −0.341). The SE elastogram and MRI findings were consistent for only MMAH (P = .044). Conclusion: Ultrasound elastography (USE) is an appropriate and valuable imaging technique that supports MRI and B-Mode US for the detection of meniscal injury. Cite this article as: Karadayı Büyüközsoy A, Voyvoda N, Fariz B, Özer T. Diagnostic accuracy of ultrasound elastography in meniscus assessment: A comparative analysis with magnetic resonance imaging. Cerrahpaşa Med J. 2024;48(2):166-171.